Preparation of 13C and 15N labelled RNAs for heteronuclear multi-dimensional NMR studies. - Nikonowicz, E P (1992)
A procedure is described for the efficient preparation of isotopically enriched RNAs of defined sequence. Uniformly labelled nucleotide 5'triphosphates (NTPs) were prepared from E.coli grown on 13C and/or 15N isotopically enriched media. These procedures routinely yield 180 mumoles of labelled NTPs per gram of 13C enriched glucose. The labelled NTPs were then used to synthesize RNA oligomers by in vitro transcription. Several 13C and/or 15N labelled RNAs have been synthesized for the sequence r(GGCGCUUGCGUC). Under conditions of high salt or low salt, this RNA forms either a symmetrical duplex with two U.U base pairs or a hairpin containing a CUUG loop respectively. These procedures were used to synthesize uniformly labelled RNAs and a RNA labelled only on the G and C residues. The ability to generate milligram quantities of isotopically labelled RNAs allows application of multi-dimensional heteronuclear magnetic resonance experiments that enormously simplify the resonance assignment and solution structure determination of RNAs. Examples of several such heteronuclear NMR experiments are shown.